2011
DOI: 10.1111/j.1547-5069.2011.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nurse Work Environment and Staffing on Hospital Nurse and Quality of Care in Thailand

Abstract: Nurses should work with management and policymakers to achieve safe staffing levels and good work environments in hospitals throughout the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
3
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 36 publications
12
103
3
8
Order By: Relevance
“…Job stress was inversely (negatively) related to the quality of patient care; this is in line with the findings of Park et al [10] that showed job stress is a threat to quality of patient care and safety. Job satisfaction had a direct relationship with quality of patient care, which is consistent with the findings of Havlovic [7] and Nantesopat et al [13]. The results of linear regression showed that job stress was the only predictor of the quality of patient care and predicted 6% of quality of patient care.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Job stress was inversely (negatively) related to the quality of patient care; this is in line with the findings of Park et al [10] that showed job stress is a threat to quality of patient care and safety. Job satisfaction had a direct relationship with quality of patient care, which is consistent with the findings of Havlovic [7] and Nantesopat et al [13]. The results of linear regression showed that job stress was the only predictor of the quality of patient care and predicted 6% of quality of patient care.…”
Section: Discussionsupporting
confidence: 80%
“…The quality of work life is comprehensive and increasing employee satisfaction and education helps them adapt to change [8]. Studies have found that the effect of different aspects of the quality of work that influence the quality of patient care include life organizational variables such as organizational conditions [9], occupational stress [10], organizational support from the medical staff [11], workload [12], job satisfaction [7,13], and occupational burnout [9,14,15]. Quality of work life can affect staff performance [16] and job engagement [17] and the factors also predict the quality of organizational service.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that professionals working in hospitals had higher scores of depersonalization and nurses working in community services had a greater sense of personal fulfillment. (5)(6)(7)(8)(9)(10)(11)(12) The exposure to conflict situations and living with violence in the workplace can contribute to the psychological burden on nursing professionals. A protective measure against the violence of patients can be implemented by the service management with appropriate therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
“…Health workforce planning and quality Our review highlights staff impact on service delivery (Nantsupawat et al, 2011;Neff et al, 2011), particularly workload and overload (Gunnarsdottir et al, 2009), good leadership (Neff et al, 2011) and nurse-physician relations Shang et al, 2012). Medical and surgical interventions are increasingly complex and there is a need for a larger and more specialised clinical workforce (Aiken et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Nantsupawat et al, (2011) Determined nurses' work environment and staffing, and its effect on nurse outcomes, job satisfaction, burnout and quality.…”
Section: Nursesmentioning
confidence: 99%